Optical Properties of Polyvinyl Alcohol (PVA) / Silver Sulfide Polymer Composites - Tahir, Dana A.; Mamand, Soran M.; Hussein, Sarkawt A.; Abdullah, Omed G.; Aziz, Shuja B. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this work silver sulfide (Ag2S) has been synthesized inside the PVA polymer by in situchemical reduction method. The UV-Visible spectrophotometer was used to study the optical properties of the prepared composite samples. The absorption spectra reveal the influence of Ag2S particles on optical behavior of PVA. There is an increase in refractive index of the samples contains Ag2S filler, and exhibits a dispersion behavior. The extinction coefficients of the composite samples are higher than that of pure PVA. The linear relationship between the refractive index athigh wavelength region and Ag2Sconcentration was observed, indicating homogeneous dispersion ofthe filler in the PVA matrix.The absorption coefficient shifts to lower photon energy at higher Ag2S concentration, in which the optical band gap will reduce.
Keywords: PVA polymer silver sulfide refractive index absorption coefficient optical band gap